FEAR OF FALLING AND LOWER LIMB CONDITIONING IN THE ELDERLY: IMPACTS ON HEALTHY AGING (CIPEEX, 2025)
Chronic-degenerative changes inherent to aging lead to a significant problem: the fear of falling, present both among fallers and non-fallers. This study aimed to analyze concern and risk of falls, fall frequency, and lower limb strength conditioning in elderly individuals over 60 years of age of both sexes. The methodology used was the application of the Falls Efficacy Scale (FES-1), which measures concern and fear of falling, asked about the number of falls in the last 12 months, and included the Sit-to-Stand physical test. The sample was recruited by convenience from groups attending a Basic Health Unit in Gurupi, Tocantins. Results: Groups that presented occasional concern about falling accounted for 38.5%, those without concern 32.9%, and those with recurrent concern 28.6%. Regarding fall frequency, 59.2% did not experience any fall, 22.1% fell once, 10.8% fell twice, and 8% fell more than three times. In the Sit-to-Stand test, 69% of the elderly presented low lower limb strength conditioning and 31% normal conditioning. The study demonstrated a considerable level of concern among the elderly, particularly those with decreased lower limb strength, regarding falling during daily basic activities.
Keywords: Fear of falling; lower limb conditioning; fall risk; elderly